IMMUNE MONITORING OF DENDRITIC CELL-BASED CANCER VACCINE IN GLIOBLASTOMA PATIENTS - Skachkova О.V.; Gorbach О.І.; Khranovska, N.M.; Glavatskyi, O.Ya.; Khmelnytskyi, H.V.; Shuba, I.M.; Shevelov, M.M.; Zemskova О.V. (World of Medicine and Biology, 2021)
The purpose of the study was to define the most informative immunological criteria for assessing the immunotherapy efficacy applying dendritic cell-based cancer vaccine in glioblastoma patients. Dendritic cell-based cancer vaccine immunotherapy does not affect significantly the count of the major populations of peripheral blood cells (T-, B- and NK-cells). The most significant changes in dendritic cell-based cancer vaccine glioblastoma patients were evident in subpopulations of CD3+HLA+- and CD38+- activated lymphocytes as well as suppressor cells (MDSC and Т-reg (CD4+25+127low)). According to ROC analysis the sufficient sensitivity and specificity were estimated for 3 biomarkers, namely the relative count of activated CD38+- and CD3+HLA+- lymphocytes and Т-reg cells. The threshold levels for the counts of these cells have been determined. The obtained results allow recommending these indices as the immunological criteria for assessing the efficacy of dendritic cell-based cancer vaccine in the treatment of glioblastoma.